Laparotomy in non Hodgkin’s lymphomas - Vázquez, Tabaré; Mate, Miguel; Viola, Antonio; Garbino, Carlos; Torres, Manuel; Decaro, Jorge; Priario, Julio C; Kasdorf, Helmut (Cirugía del Uruguay, 1976)
The authors present their experience and findings with staging laparotomy in 15 patients with nonHodgkin's lymphoma, during four years (1971-1975). The median age of the patients was 39,4 years. Seven were males and eight women. Diagnosis in all cases was confirmed by histopathology and classified m accordance with Rappaport. Lesions predominated in supradiafragmatic Iymph nades and high aero-digestive tract (13/15 cases). In this group, after laparotomy, 38,4 % advanced in the clinicopathological classification, from stage I to stage III. Only in 6 cases bipodal lymphangiography could be done, but only in -one of these patients tumoral lymph nades could be seen at the leve! of the lymph nade axis; on the contrary 7 /15 laparotomi,ied patients ( 46,6 % ) presented tumoral lymph nades outside the lymph nade axis, so that they could not be seen radiologically. Morbimortality of laparotomy until 30 days was none. The importance of this technique far the clinicopathological staging is enfathized, but insisting that far stage II non regional, stage III and IV it is not justified to employ it systematically. Instead, it is a most useful method in stage I and stage II regional, because it permits the finding of intraabdominal tumoral lymph nades that could not be proved by other paraclinical studies, implying this modifications in the previous clinico-pathological classification; since staging is more advanced a change to therapeutic schedules more appropiated to the real extension of the disease is necessary.